Effects of acute aerobic exercise with self-selected music on working memory and alpha oscillation. - Tsai, Yu-Jung; Chueh, Ting-Yu; Catalán, David Garrido; Hsieh, Shu-Shih; Hung, Tsung-Min (International Journal of Sport & Exercise Psychology, 2024)
This study investigated the effects of exercise while listening to music on behavioural performance and electroencephalogram of working memory (WM). The within-subjects crossover posttest comparison design was used, and 37 participants were recruited to perform the following three sessions in a counterbalanced order: 30-minute bout of exercise while listening to music (Ms), exercise without music (Ex), and control condition (Cn). Exercise intensity was defined as within 40–60% of maximal heart rate and a tempo of 125–140 bpm was used as the qualification for selecting music. After each session, lower and upper alpha event-related desynchronisation (ERD) was measured during auditory WM. Affective response analysis showed that Ms and Ex induced positive mood in participants compared to Cn. Ms had lower rate of perceive exertion compared to Ex and only Ex had lower tranquility from post-exercise to pre-exercise, indicating relatively more effort and less calm following Ex. behavioural analysis showed that Ms had shorter reaction time compared to Cn, indicating better WM performance following Ms. Upper Alpha ERD analysis showed a task effect on Cn instead of Ms or Ex. Generally, exercise with self-selected music can make exercising more enjoyable and effortless, while reaping the additional benefits of enhanced WM to efficiently retain and manipulate information from daily tasks.